Comparison of Sequence Variants in the PDK4 and COX412 Genes Between Racing and Cutting Lines of Quarter Horses and Associations With the Speed Index - Pereira, Guilherme L. [UNESP]; Matteis, Rafael de [UNESP]; Meira, Camila Tangari; Regitano, Luciana C. A.; Silva, Josineudson Augusto V.; Chardulo, Luis Arthur L.; Curi, Rogerio A. (Elsevier B.V., 2016)
Different selection objectives within the Quarter Horse breed led to the formation of groups with distinct skills, including the racing and cutting lines. With a smaller population size in Brazil, but of great economic representativeness, the racing line is characterized by animals that can reach high speeds over short distances and within a short period of time. The cutting line is destined for functional tests, exploring skills such as agility and obedience. Although the athletic performance of horses is likely to be influenced by a large number of genes, few genetic variants have so far been related to this trait and this was done exclusively in Thoroughbreds, including the g.38973231G>A single nucleotide polymorphism in the PDK4 gene and the g.22684390C>T single-nucleotide polymorphism in the COX412 gene. The results of the present study demonstrate the presence of polymorphic PDK4 and COX412 genes in Quarter Horses. The analysis of 296 racing animals and 68 cutting animals revealed significant differences in allele and genotype frequencies between the two lines. The same was not observed when these frequencies were compared between extreme racing performance phenotypes. There were also no significant associations between alleles of the two polymorphisms and the speed index. These results suggest that the alleles of the PDK4 and COX412 genes, which are related to better racecourse performance in Thoroughbreds, are probably associated with beneficial adaptations in aerobic metabolism and therefore play secondary roles in sprint racing performance in Quarter Horses, which is mainly anaerobic. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Candidate gene; Equine; Polymorphism; QTL; SI